Phase-transfer catalysis - Starks, Charles M. (NA Springer, 2010)
This book is the definitive reference on phase-transfer catalysis (PTC), written by the three foremost industrial and academic PTC experts in the world. Phase-Transfer Catalysis, the first practical guide to performing PTC in industry, includes key information and analyses found in no other publication. It will be a valuable resource for synthetic organic chemists, polymer chemists, process chemists, developmental chemists, and chemical engineers in academia and industry. Organic process chemists seeking greater process flexibility, reduced manufacturing costs and pollution, and easier compliance with environmental regulations will find it an indespensable reference. The book provides a thorough introduction to the fundamentals of PTC as a synthetic organic chemistry technique, including reaction mechanisms, selectivity, rates and kinetics. It gives specific guidelines on how to optimize catalyst, solvent, base, hydration, and more, based on reaction characteristics. The section on applications includes nucleophilic displacement reactions, oxidation and reduction reactions, and such special topics as insoluble PTC (triphase catalysis), polymerization, chiral catalysis, applications in environmental and analytical chemistry, and transition metal co-catalyzed PTC. Throughout the book, PTC applications in key industries are discussed--including organic chemicals, polymers, pharmaceuticals, agrichemicals, monomers, petrochemicals, flavors and fragrances, additives, dyes, and specialty chemicals.
Keywords: PHARMACEUTICAL CHEMISTRY